The Effect of Combination of Tubifex sp and Artificial Feed on the Growth and Molting of Giant Shrimp (Macrobrachium Rosenbergii) Stadia V. - Dianita Wijayanti; Ganjar Adhywirawan Sutarjo; Riza Rahman Hakim (Universitas Muhammadiyah Malang, 2020)
Giant Prawns (Macrobrachium rosenbergii) or freshwater prawn is also one of the crustaceans, which has the largest size compared to other freshwater prawns, in addition to giant prawns have a high economic value. The obstacle to the giant prawn's cultivation is determining the combination of natural and artificial feeding for giant prawns to improve molting quickly and increasing the growth of giant prawns. The method used was the experimental method, Completely Randomized Design (RAL) with five treatments: P1 (100 % Pellet), P2 (25 % Tubifex + 75 % Pellet), P3 (75 % Tubifex + 25 % Pellet), P5 (100 % Tubifex) and 3 replications. The data were analyzed using diversity analysis (ANOVA), and if there were differences it could be continued with the BNT test. The results showed that The Influence of Tubifex sp and Natural Feeding Percentage And Artificial Feeding On Moulting Acceleration And Growing Giant Prawns/Crawfish (Macrobrachium Rosenbergii) Stadia V greatly influenced the molting of giant prawns. The water quality during the study ranged from 23˚C-29˚C, dissolved oxygen 3,6-8,7 mg/l, and pH ranged from 7.3 to 8.9. The conclusions from the 30-days of study obtained the highest results for molting on the second treatment (P2) was 0.43, while the fourth treatment (P4) was the best combination in weight growth with a value 6390,42 mg, and long growth showed that the fourth treatment (P4) also gave the highest result which is 406.75 mg.